India and the world through the eyes of Indian diplomats/ edited by Surendra Kumar (New Delhi, 2015)
If there in anything constant in the world, it is change, especially in today's globalised world. Thirty mandarins of the South Block look at the current changes in different parts of the world, try to connect them with developments of the recent past, analyse and dissect them with experience and understanding spanning decades and strive to foresee what's likely to happen and weigh how that could impact India's relations with the rest of the world. This book is a unique treasure of thoughts and ideas of Indian diplomats who have collectively put in more than 1150 years in Indian Foreign Service, representing three generations: those who joined in 1950s, in the 1960s and the 1970s. While some have shared reflections and reminiscences of their roller coaster journey of diplomatic career, others have focused on India's relations with different countries and regions. A few have set out on a rather philosophical mode wondering whether it's hard power or the soft power or the soul power that serves national interests best and whether the days of quiet diplomacy are numbered. All in all, it's a heady cocktail of reflections and reminiscences, hardnosed analysis and dispassionate interpretation and, of course, some crystal ball gazing. This distinctive study of international relations and contemporary history offers thought-provoking ideas and will not just benefit practitioners and informed students of foreign affairs but the general readers as well.
Keywords: Diplomats